Breastfeeding practices among long-standing refugees in Jordan: insights from a cross-sectional study - Qasem, Nuha; Al-Shdaifat, Amjad; Abu-Khader, Deema; Jaraa, Sajeda; AlOthman, Jelan; Shatat, Lina; Alsaif, Lara (Frontiers in Public Health, 2025)
Exclusive breastfeeding (EBF) is a crucial public health strategy that reduces infant morbidity and mortality, yet rates remain suboptimal among refugee populations. This study examines breastfeeding practices and determinants of EBF among long-standing Palestinian refugees in Jordan through a cross-sectional survey of 249 mothers at the UNRWA Zarqa Camp Health Center. The prevalence of EBF among infants under 6 months was 38.2%, declining with age. Key predictors included birth order, mode of delivery, labor analgesia, and breastfeeding initiation timing. Mothers who delivered vaginally avoided analgesia, and initiated breastfeeding within the first hour had significantly higher EBF rates. Perceived insufficient milk supply was the primary reason for formula introduction. Breastfed infants experienced fewer acute illnesses, antibiotic use, and allergic conditions. Despite moderately positive maternal attitudes toward breastfeeding, fewer than half of the mothers received breastfeeding education, with no significant association between maternal knowledge and feeding methods. These findings underscore the need for interventions promoting early breastfeeding initiation, reducing unnecessary cesarean sections and analgesia, and strengthening breastfeeding education to improve EBF rates and infant health in refugee settings.